TANGGUNG JAWAB PERUSAHAAN PENGANGKUTAN TERHADAP BARANG KONSUMEN (STUDI KASUS DRIVER GOJEK MEMBAWA LARI BARANG KONSUMEN) - Palit, Natalia Evira; Ansari, Teuku Syahrul (Jurnal Ilmiah Wahana Pendidikan, 2024)
Along with technological developments, GoSend in Gojek provides services to provide 24-hour delivery of goods and documents that consumers can order online and can reach their destination faster than conventional goods delivery services. However, every delivery service still has the risk of loss or damage to goods as happened on August 12, 2001, the case of loss of goods of GoSend service users who were taken away by Gojek drivers. This study aims to determine the liability of the company PT Gojek Indonesia for consumer goods. The research method used is normative legal research. Data is collected from legal sources by reviewing legislation and literature studies with credible sources such as books, journals, and written documents. The results show that the laws and regulations used for insurance and freight transportation agreements are contained in Articles 86-97, Article 246, Article 466-517c. Meanwhile, consumer protection is regulated in UU Nomor 8 Tahun 1999. Meanwhile, based on the case studied, PT Gojek Indonesia provides compensation for the loss of goods experienced by consumers with a nominal amount in accordance with the purchase invoice. This shows that Gojek has shown corporate responsibility. Translated with DeepL.com (free version)